Growth aspects of the marine microalga Nannochloropsis gaditana - Rocha, Jorge M. S. (2003)
Nannochloropsis is well appreciated in aquaculture due to its nutritional value and the ability to produce valuable chemical compounds, such as pigments (zeaxanthin, astaxanthin...) and polyunsaturated fatty acids (EPA). Commercial exploitation needs high cell densities but the low growth rate and the small size of cells are practical difficulties. To increase biomass concentration the positive effect of several factors was evident: (i) pH[approximate]8 control (with dilute Tris-HCl buffer); (ii) the continuous illumination (no evidence of photo-inhibition was observed); (iii) a quite large temperature range (25±5 °C); (iv) the presence of organic carbon source (with the danger of contamination); (v) the presence of urea as an additional nitrogen source (10 mM); (vi) a small air flow rate with large bubbles can be more efficient for CO2 mass transfer (associated to reduced shearing).